An approach for evaluating tensile strength of painted steel plates from the surface rusting grade. (3rd October 2018) - Kim, Hyoung-Seok; Jeong, Young-Soo; Dao, Duy Kien; Kim, In-Tae
ABSTRACT: The level of anticorrosive performance is easy to determine from visual inspections of painted steel structures, but the structural performance level is difficult to evaluate. In this study, a tensile test was carried out on structural steel plates with pitting corrosion. Artificial defects were made with percentages of rusted surface area of 0, 3, 10, 16, 33 and 50% and depth-to-radius aspect ratios of 0.25, 0.5 and 1.0. From the test results, the relationship among the percentage of rusted surface area, the aspect ratio and tensile strength was defined. Accordingly, a simple approach is proposed for evaluating the tensile structural performance level from the visual inspection of painted steel structures.